Effects Of Long Chain N-3 Polyunsaturated Fatty Acids Supplementation On Development Of Cognitive Function In Rats - Ahmad, Hafandi (2007)

(untitled)
The effects of long-chain polyunsaturated fatty acid (LC-PUFA) supplementation on cognitive function development in rats were evaluated in three interlinked experiments. In Experiment I, twenty eight three-month old female Sprague-Dawley rats were allocated equally into four treatment groups. Rats were fed either rat chow only (Control group, n=7), rat chow containing 10% (w/w) butter (BT group, n=7), rat chow added with 6.66% (w/w) menhaden oil and 3.34% (w/w) soybean oil (M3 group, n=7) and rat chow added with 3.34% (w/w) menhaden oil and 6.66% (w/w) soybean oil (S6 group, n=7) diets. All rats were fed for six weeks and the individual body weights were recorded weekly to obtain their body weight gain between week-0 to week-6. Baseline observations for the spatial mental ability were acquired using the Morris Water Maze (MWM) test. Plasma fatty acid (FA) profiles were also assayed using chromatographic techniques. Results showed that after six weeks of treatments, there were statistically significant improvements in path length and time to reach the hidden platform. Rats in the M3 group showed a shorter path length and duration (P<0.05) to swim and reach the platform than those in the S6, BT and Control groups. The M3 group which was fed with a high level of menhaden oil rich in docosahexaenoic acid (DHA) performed better on path length and time to find the hidden platform. Blood plasma FA profiles mirrored the dietary FA composition. The plasma and tissues of the M3 animals also had significantly increased (P<0.05) levels of polyunsaturated fatty acids (PUFAs) at the end of the trial, compared to both BT and Control groups. The n-6:n-3 PUFA ratio was 0.9 in the M3 group and was lower than the other groups. Results indicated that the dietary n-3 PUFA supplementation produced a better performance in the MWM test and tissue FA profile as well. Experiment II was designed to determine the effects of maternal n-3 supplementation on plasma FA profile and mental ability performance in the second generation offsprings. All rats (n=28) from Experiment I were given the same treatment diet throughout the entire experiment period. This included two weeks of acclimatization period, three weeks of gestation and throughout the entire lactation period of six weeks. After parturition, pups were separated on day 21 according to their sex. On postnatal day four, blood plasma was collected from all pups (n= 20) via cardiac puncture. Milk samples were obtained from dams for FA profile determination. All pups were than treated with the same treatment diet as their dams upon weaning. On postnatal day 21, all pups (n=20) were tested for mental ability using the MWM test and animal behavior scores. Results showed that the n-3 supplemented M3 pups had significantly better performances in the MWM test (P<0.05). The M3 pups also had significantly better animal behavior scores such as open field activity and maternal behavior. Fatty acid profiles were closely related to the maternal plasma FA profiles. High maternal dietary intake of n-3 PUFA such as menhaden oil increased the level of DHA in milk and plasma, particularly in the M3 group. The n-6:n-3 ratio was lower in the M3’s milk at 4.7 compared to the other groups. This indicated that blood plasma played a major role in the transport of DHA from the placenta to the fetus. In addition, results showed that the rats (n=7) on the M3 group had significantly higher levels of docosahexaenoic acid at 6.1% (341.2±86.4 mg/100ml) and total n-3 PUFA at 30.0% in their plasma after week-15. Experiment III attempted to determine the effects of n-3 PUFA supplementation on distribution and neuronal histology. After one year of induction period, all rats from first and second experiment (Dams, n=28 and Pups, n=20) were sacrificed and the whole brain were removed and weighed. Brain tissues were fixed for histological examinations. The brain weight of the M3 and S6 groups were significantly lower than the butter-supplemented BT group (P<0.05). However, neuronal density was highest among the n-3 supplemented M3 dams and pups. These results reaffirmed that n-3 PUFA supplementation affects neuronal and brain development associated with learning performance in rats. In summary, dietary n-3 PUFA supplementation promoted the development of cognitive function or mental ability in rats. This was achieved via structural and functional changes in neurons involved in learning and spatial memory in the experimental subjects.